PENGARUH INTELIGENSI, KELENTUKAN, DAN MOTOR EDUCABILITY TERHADAP HASIL BELAJAR JURUS TUNGGAL PENCAK SILAT - Aridhotul Haqiyah; Dani Nur Riyadi (Perspektif Ilmu Pendidikan, 2018)
The background to this research is the unfavorable of the learning outcomes in pencak silat single artistic. The purpose this research was to determine the effect of intelligence, flexibility, and motor educability of the learning outcomes in pencak silat single artistic student on Unit Kegiatan Mahasiswa Pencak Silat Islamic University â€œ45â€. This research was conducted at Islamic University â€œ45â€ Bekasi, Jl. Cut Meutia No. 83 Bekasi in November 2016 with survey method, technical analysts use path analysis. The population this research is the student on Unit Kegiatan Mahasiswa Pencak Silat Islamic University â€œ45 amount to 30 people. The sampling technique used purposive sampling amounted to 16 people. The instruments used are learning outcomes in pencak silat single artistic used assessment rubric scale of 3 (good, enough and less), an intelligence test, sit and reach test, and Motor Educability Iowa Brace Test. The conclusion is: (1) Intelligence directly affects the learning outcomes of pencak silat single artistic, (2) flexibility has no directly affects the learning outcomes of pencak silat single artistic, (3) Motor educability directly affect the the learning outcomes of pencak silat single artistic, (4) Intelligence directly affects the motor educability, and (5) flexibility directly affects the motor educability. ReferencesArikunto, S. (2013). Prosedur penelitian suatu pendekatan praktik. Jakarta: PT. Rineka Cipta.Badriah, D.L. (2009). Fisiologi olahraga edisi II. Bandung: Multazam.Edwards, H. W. (2011). Motor learning and control: Form theory to practice. USA: Wadsworth.Haqiyah, A., & Mulyana., et al. (2017). The effect of intelligence, leg muscle strength, and balance towards the learning outcomes of pencak silat with empty-handed single artistic. JETL (Journal of Education, Teaching And Learning), 2, 211-217. doi: http://dx.doi.org/10.26737/jetl.v2i2.288Haqiyah, A. (2016). Pengaruh inteligensi, kekuatan otot tungkai, dan keseimbangan terhadap hasil belajar jurus tunggal tangan kosong pencak silat. PERSPEKTIF Ilmu Pendidikan, 30(2), 125-134. doi: https://doi.org/10.21009/PIP.302.7Hasil MUNAS XII IPSI. (2007). Peraturan pertandingan pencak silat. Diakses melalui https://ipsibalikpapan.files.wordpress.com/2011/04/peraturanpertandinganpencaksilat.pdfKadir. (2015). Statistika terapan. Jakarta: Rajawali Pers.Kuswana, W.S. (2014). Biopsikologi pembelajaran perilaku. Bandung: Alfabeta.Lubis, J. & Wardoyo, H. (2014). Pencak silat edisi kedua. Jakarta: Rajawali Sport.Nuraini, S. (2014). Hasil belajar jurus tunggal pencak silat tangan kosong, studi eksperimen tentang gaya mengajar, umpan balik dan motor educability pada mahasiswa Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta. Disertasi. Jakarta: Universitas Negeri Jakarta.Schmidt, R.A. (2000). Motor control and learning. United State America: Human Kinetics.Schmidt & Wrisberg. (2000). Motor learning and performance. Champaign: Human Kinetics.Soemanto, W. (2012). Psikologi pendidikan landasan kerja pemimpin pendidikan. Jakarta: Rineka Cipta.Tangkudung, J. (2012). Kepelatihan olahraga. Jakarta: Cerdas Jaya.Van der Fels, I.M.J. & C.M te Wierike, S., et al. (2015). The relationship between motor skill and cognitive skills in 4-16 years old typically developing children: A systematic review Elsevier. Journal of science and medicine in sport, 18(6), 697â€“703. doi: https://doi.org/10.1016/j.jsams.2014.09.007Widiastuti. (2015). Tes dan pengukuran olahraga. Jakarta: Rajawali Pers.Zubaidi, A. (2009). Tes inteligensi. Jakarta: Mitra Wacana Media.